Arbitration in China : a legal and cultural analysis - Fan, Kun (Hart Publishing, 2013)
Written for international businessmen, lawyers, academics and students, this book gives the reader a unique insight into real arbitration practice in China, based on a combination of theoretical analysis and practical insights.
Keywords: Arbitration and award -- China.; Dispute resolution (Law) -- China.; Mediation -- China.; Règlement de conflits -- Chine.; Médiation -- Chine.; Arbitrage (Droit) -- Chine.; International arbitration.; Law -- Arbitration, Negotiation, Mediation.; Arbitration and award; Dispute resolution (Law); Mediation; China